2021
DOI: 10.3390/ijms22168577
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Receptor Binding Inhibitors with In Vivo Efficacy against Botulinum Neurotoxin Serotypes A and E

Abstract: Botulinum neurotoxins (BoNTs) are the most poisonous substances in nature. Currently, the only therapy for botulism is antitoxin. This therapy suffers from several limitations and hence new therapeutic strategies are desired. One of the limitations in discovering BoNT inhibitors is the absence of an in vitro assay that correlates with toxin neutralization in vivo. In this work, a high-throughput screening assay for receptor-binding inhibitors against BoNT/A was developed. The assay is composed of two chimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…All recombinant antigens contained 6xhis tag. The proteins were expressed and purified as described previously (18)(19)(20).…”
Section: Recombinant Proteins and Toxinsmentioning
confidence: 99%
“…All recombinant antigens contained 6xhis tag. The proteins were expressed and purified as described previously (18)(19)(20).…”
Section: Recombinant Proteins and Toxinsmentioning
confidence: 99%
“…BoNTs are the most toxic biotoxins, which can cause nerve paralysis syndrome in mammals and other vertebrates, and are classified as class A biological warfare agents by the US centers for disease control and prevention (CDC) [ 3 , 4 ]. According to the neutralization effects of specific antisera, BoNTs can be divided into seven traditional serotypes, A–G, and novel botulinum neurotoxins, including BoNT/H (previously considered to be a chimeric neurotoxin of BoNT/F and BoNT/A) and BoNT/X [ 5 , 6 , 7 , 8 , 9 ]. Among them, botulinum neurotoxin serotypes A, B, E, and F cause human poisoning, while BoNT/C and D cause neurotoxicity in animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al [ 51 ] in their study have shown their two 8-hydroxyquinoline candidate compounds: NSC1011 and NSC1014 to have remarkable extension in survival in mice models against BoNT/F challenge. Receptor binding inhibitor molecules like aurintricarboxylic acid (ATA) provided protection against BoNT A/E challenge [ 52 ]. These novel molecules and approaches hold promise towards a concluding therapeutic for BoNT spectrum pathogenesis (Table 4 ).…”
Section: Introductionmentioning
confidence: 99%